Effects of naturally occuring phenolic compound on cell wall degrading enzymes and suppression of Ganoderma boninense infection in oil palm seedlings - Surendran, Arthy (2018)
Palm oil is one of the major sources of edible oil in the world with 85% of it being produced by Malaysia and Indonesia. However, the production is greatly hindered by the basal stem rot (BSR) disease. The causal pathogen of BSR disease is Ganoderma sp. Ganoderma boninense, the causal pathogen of BSR in oil palm is white rot basidiomycetes. This pathogen infects oil palm primarily via roots by degrading the lignin and cellulose components. Therefore, understanding the mode of infection of G. boninense in oil palm would be advantageous. An alternative solution to control the emergence of BSR is to inhibit the lignolytic and the cellulolytic enzymes of G. boninense. The phenolic compounds present naturally in the plants play a critical role in the pathogen elimination, signaling, increasing the resistance and the lignin biosynthesis. Hence, ten naturally occurring phenolic compounds namely, benzoic acid, coumaric acid, 2,6-dimethoxyl benzoic acid, 2,6-dimethoxyl phenol, guaiacol, ferulic acid, pyrocatechol, salicylic acid, syringic acid, and vanillic acid were selected to evaluate their potential to inhibit G. boninense. In this study, the phenolic compounds were tested for their ability to inhibit the growth of G. boninense and their inhibitory effect towards the production of lignolytic and cellulolytic enzymes. Further, their efficacy was tested to suppress the BSR infection in oil palm seedlings. The ten selected phenolic compounds were able to inhibit the growth of G. boninense with different degrees depending on their concentrations. Microscopic observations revealed that mycelia growing on media containing phenolic compounds showed deterioration. A significant (p ≤ 0.05) decrease in the production of lignolytic enzymes, as well as celluase, amylase and xylanase of about 40-100% was identified. Except benzoic acid all the other phenolic compounds increased the secretion of lignolytic and cellulolytic enzymes at 1 mM concentration. However, as the concentrations increased more than 1 mM the inhibition increased. The enzyme inhibitions have been further quantified and the type of inhibition was analysed along with their physicochemical properties. Most of the selected phenolic compounds inhibited the enzymes as uncompetitive or noncompetitive inhibitors. The lignolytic enzymes were active over a wide range of temperature from 40-80ºC but sensitive to pH at 6. The cellulolytic enzymes are more stable in a wide range of pH from 3 to 8 and temperature 40-80ºC when compared to the lignolytic enzymes. The wood degradation assay suggested that the G. boninense is a sequential degrader of lignin and cellulose components. The selected phenolic compounds significantly reduced the degradation rate upto 100% when compared to the control. This was due to their ability to inhibit the lignolytic and cellulolytic enzymes of G. boninense. Significant reductions in the disease progression upto 100% were observed in the oil palm seedlings treated with benzoic and salicylic acid. The oil palm seedling treated with benzoic and salicylic acid increased the growth parameters such as height, diameter of the stem, chlorophyll content, root and shoot weight. In addition, the oil palm seedlings treated with phenolic compounds showed increased lignification of four percentages. This was due to the increased activity of phenylaline amino- lyases, peroxidase and polyphenol oxidase by 1.5 folds. These enzymes are known to be involved in lignin biosynthesis pathway. The benzoic acid and salicylic acid tested are the processors for the synthesis of lignin. The findings of this study could be useful for developing new strategies in controlling the spread of disease, which may reduce the BSR disease severity in oil palm areas of production.